2007
DOI: 10.1534/genetics.106.063693
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping Reveals Sex Bias in Quantitative Trait Loci Affecting Growth, Skeletal Size and Obesity-Related Traits on Mouse Chromosomes 2 and 11

Abstract: Previous speed congenic analysis has suggested that the expression of growth and obesity quantitative trait loci (QTL) on distal mouse chromosomes (MMU) 2 and 11, segregating between the CAST/EiJ (CAST) and C57BL/6J-hg/hg (HG) strains, is dependent on sex. To confirm, fine map, and further evaluate QTL 3 sex interactions, we constructed congenic by recipient F 2 crosses for the HG.CAST-(D2Mit329-D2Mit457)N(6) (HG2D) and HG.CAST-(D11Mit260-D11Mit255)N(6) (HG11) congenic strains. Over 700 F 2 mice were densely g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 48 publications
3
49
0
Order By: Relevance
“…Such interactions between QTLs and sex were also observed in other obesity-related studies in mice, [42][43][44][45] suggesting that underlying genes were differentially expressed in males and females. For example, estrogens that differ between the two sexes can act as transcription factors and might regulate the QTL alleles in a sex-specific manner.…”
Section: Discussionsupporting
confidence: 76%
“…Such interactions between QTLs and sex were also observed in other obesity-related studies in mice, [42][43][44][45] suggesting that underlying genes were differentially expressed in males and females. For example, estrogens that differ between the two sexes can act as transcription factors and might regulate the QTL alleles in a sex-specific manner.…”
Section: Discussionsupporting
confidence: 76%
“…A significant interaction was also detected for the putative body mass QTL on chromosome 23 but this result remains speculative because of uncertainties regarding the presence of a QTL at that position. QTLs with sex-specific effects have been documented in a variety of organisms (for example, Nuzhdin et al, 1997;Farber and Medrano, 2007;Moghadam et al, 2007) including domestic sheep ), but to our knowledge had never been documented in a free-living wildlife population. The presence of sex-specific QTL effects in bighorn sheep adds to the accumulating evidence suggesting that sexual selection alters the genetic architecture of quantitative traits by promoting the accumulation of sex-specific genetic variance (Moller 1993;Wilkinson 1993;Bonduriansky and Rowe, 2005;Wright et al, 2008;Robinson et al, 2009).…”
Section: Sexâqtl Interactionsmentioning
confidence: 91%
“…Likewise, two other QTLs were novel (Bwtq13 and Adip19), although in the case of Adip19, there were a few points to consider before we concluded that this was a novel QTL. There were three previous reports of QTLs near Adip19 but all previous QTLs had features that made it unlikely that they captured the same underlying genetic variation (Carlborg et al 2005;Collin et al 2005;Farber and Medrano 2007). Determining whether a QTL replicates is subject to some uncertainty regarding its location, confidence interval, and its effects on a particular genetic background, and thus the term "novel QTL" is applied here only with these considerations in mind.…”
Section: Novel Qtlsmentioning
confidence: 99%
“…In addition to the types of obesity measures used, the strength of sex-by-genotype (Farber and Medrano 2007) and gene-gene interactions (Brockmann et al 2000) influence the trait. These types of interactions may be as important as additive genetic effects in their contribution to the heritability of body composition.…”
Section: Introductionmentioning
confidence: 99%